CO2 Capture via Adsorption Using Silica Gel - Pérez-Rial, Leticia; Alfonsín, Víctor; Maceiras, Rocío; Feijoo, Jorge; P. Vallejo, Javier (European Journal of Sustainable Development, 2024)
This paper investigates the potential of silica gel as an effective adsorbent for CO2 capture. The study explores the adsorption mechanisms, the efficiency of CO2 uptake, and some factors influencing the adsorption capacity of silica gel. The experimental results demonstrate the significant potential of silica gel for CO2 adsorption under various conditions. The adsorption capacity was found to be highly dependent on parameters such as gas flow rate and the particle size of silica gel. The findings suggest that with optimized conditions, silica gel could be a viable material for reducing atmospheric CO2 levels. This research contributes to the development of sustainable and efficient technologies for mitigating climate change through carbon dioxide capture and storage. Keywords: CO2 capture, adsorption, efficiency, silica gel